Construct validity of a dietary protein assessment questionnaire to explore college students’ knowledge and attitudes towards dietary protein - Gutjahr, Parker; Warren, Cynthia; Miketinas, Derek (Frontiers in Nutrition, 2023)
Introduction: Misconceptions about dietary protein may exist due to unscientific information from commonly used sources such as social media. Understanding knowledge and attitudes towards protein is important for developing effective interventions to improve the dietary behaviors of U.S. college students. The objective of this study was to develop a questionnaire to evaluate college students' knowledge and attitudes towards dietary protein. Methods: The questionnaire had 64 questions, including 8 demographic, 24 knowledge, 14 attitude, and 18 behavior questions. Construct validity of the knowledge questions was assessed by performing known-group comparisons using an independent t-test. Exploratory factor analysis (EFA) with principal axis factoring and a promax rotation was used to evaluate the factor structure of the attitude questions. Results: Four hundred seventy participants (87.3% female) provided responses for the attitude questions. Fifty-five nutrition and 51 non-nutrition students provided responses for the knowledge questions. Three factors were retained: animal versus plant protein sources relationship with human and environmental health (Factor 1); organic protein sources (Factor 2); and adequacy of the protein Recommended Dietary Allowance (RDA) for weight loss and vegetarian diets (Factor 3). Mean knowledge responses were 66.4 + 11.5% and 47.6 + 16.4% for nutrition and non-nutrition students, respectively (t-test p-value for difference < 0.001). Conclusions: Protein attitudes appear multidimensional and correlated. Further testing is needed to confirm the three-factor model and to assess temporal reliability.